За Волгой земли для нас не было: записки снайпера / В. Г. Зайцев - Зайцев В. Г. (Отрочество, 1981)
Экземпляры: б/ф-10 (20131106) / Инвентарный номер: 1103 / Цена: 0.30 / Авт.знак: З-17 / ББК: 84 (2Рос=Рус)6